Career Choice: A Case Study of College Students Shifting Career Paths - Genebelle M. Lao; Desiree Janine F. Villamayor; Finlay Whea H. Campos; Jean Paul D. Dechavez; Candellen Biadoma-Toledo; Hanz Alecz Q. DasmariÃ±as (Universitas Pendidikan Indonesia (UPI), 2023)
This study aimed to determine the causes, impacts, and varying perspectives of how two years of education can alter a person's ambitions. A qualitative research design, specifically the case study approach was used in this study. It focused on why the participants enrolled in a college program that was not aligned with their SHS Strand. The responses are subsequently transcribed and themes are identified. Students whose college courses do not correspond to their Senior High School strands have questioned their previous strand selection. This is due to difficulties they encountered as a result of the misalignment. According to the general findings, one of the most important factors to consider when choosing a career is one's interest. It was also evident within the data presented that the finances and practicality of the predetermined college courses that the students chose were weighed into their decision-making. It also shows that the majority of the participants agreed that their families have an impact on their career choices. The study also discovered that doing things that are not one's passion in the first place can be difficult, but it can help people challenge their abilities. The study concludes that indeed, pre-coaching strategies and guidance provided by schools play a large factor in students' awareness of their strengths and weaknesses. Also, setting goals may make the desired changes more difficult; however, the participants rediscovered their inclination and satisfaction with what they have pursued now, which motivated them to continue.